Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea) - Páll-Gergely, Barna; Hunyadi, András; Grego, Jozef; Reischütz, Alexander; Auffenberg, Kurt (Zootaxa, 2021)
Nineteen new species of the alycaeid genera Chamalycaeus, Dicharax, and Metalycaeus are described from Thailand and Myanmar: Chamalycaeus buaboke Páll-Gergely & A. Reischütz, n. sp., C. erawan Páll-Gergely & Hunyadi, n. sp., C. hirpex Páll-Gergely & A. Reischütz, n. sp., C. irmatallus Páll-Gergely, n. sp., C. krabiensis Páll-Gergely & A. Reischütz, n. sp., C. serratus Páll-Gergely & Auffenberg, n. sp., C. spiratus Páll-Gergely, n. sp., Dicharax (?) admirandus Páll-Gergely & Auffenberg, n. sp., D. cyclostoma Páll-Gergely, n. sp., D. ebrius Páll-Gergely & Auffenberg, n. sp., D. (?) gnomus Páll-Gergely, n. sp., D. mirounga Páll-Gergely, n. sp., D. ovatus Páll-Gergely & Auffenberg, n. sp., D. subroseus Páll-Gergely, n. sp., D. verrucosus Páll-Gergely & Hunyadi, n. sp., Metalycaeus anas Páll-Gergely & A. Reischütz, n. sp., M. aries Páll-Gergely & Auffenberg, n. sp., M. bicarinatus Páll-Gergely & Hunyadi, n. sp., M. pygmachos Páll-Gergely & Hunyadi, n. sp. Alycaeus kengtungensis Godwin-Austen, 1914 is moved to the synonymy of Metalycaeus heudei (Bavay & Dautzenberg, 1900). We also report exact localities of Dicharax ataranensis (Godwin-Austen, 1914), Dicharax notus (Godwin-Austen, 1914), and Dicharax omissus (Godwin-Austen, 1914). The new records extend the known distribution of Chamalycaeus and Metalycaeus in Thailand.